Topological phase transition induced by gain and loss in a photonic Chern insulator - Teo, Hau Tian (2022)
We present a design of a non-Hermitian photonic Chern insulator whose band topology can be tuned via gain and loss. It is found that, by continuously varying the gain and loss parameter, a topological phase transition can take place in the photonic crystal, accompanied by the closing and reopening of a Dirac cone. We demonstrate this phenomenon through numerical simulations of the bulk and the edge dispersions, and steady field distributions excited by a point source. Our results show the possibility of non-Hermitian control over band topology in a Chern insulator setting and may find applications in active topological photonic devices.